Diversity and Adaptation of Islamic Law in Indonesia: Pathways to Integration - Kristinawati, Adjeng; Noviati Sri Racha; Neneng Nurhasanah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The development of Islamic law in Indonesia reflects a complex trajectory shaped by historical encounters, colonial interventions, and post-independence reforms. Its position within a plural legal system—where Islamic law coexists with state law and customary law—demonstrates both continuity and adaptation. Purpose: This study seeks to analyze how Islamic Diversity, influenced by cultural, organizational, and socio-political factors, shapes the pathways of Islamic law’s adaptation and integration in Indonesia’s national legal framework. Methods: The research applies a normative legal approach that combines historical, conceptual, and statutory analysis. Primary sources include statutory regulations and legal documents, supported by secondary materials such as scholarly literature, while tertiary sources provide definitional and contextual support. Data are analyzed qualitatively to assess the meaning and implications of legal developments. Findings: The findings reveal that Islamic law has gradually transformed from marginalization under colonial rule to significant recognition within national law through instruments such as the 1974 Marriage Law, the Compilation of Islamic Law, and Aceh’s Qanun. Ongoing debates—such as interfaith inheritance—illustrate the continuing challenges of legal pluralism and the necessity of contextual interpretation . Theoretical and Practical Implications: the study enriches scholarship on legal pluralism by demonstrating Indonesia’s unique model of integration. Practically, it highlights the maqāṣid al-sharīʿah approach as a normative tool to ensure justice, inclusivity, and responsiveness in policy and legal reform Originality/Novelty: This research contributes by integrating historical, normative, and sociological perspectives to show how Islamic Diversity can serve as a foundation for inclusive legal pluralism and sustainable legal reform in Indonesia